Investment Regulation through Trade Agreements:Lessons from Asia - Pierre Sauve (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
This article takes stock of recent trends in the investment dimensions of deepening economic integration in Asia.
Keywords: F1; 330; Investment; Regulation; Trade Agreements; Lessons; Asia